Novel BRAF Alteration in a Sporadic Pilocytic Astrocytoma - Sonika Dahiya; Jinsheng Yu; Aparna Kaul; Jeffrey R. Leonard; David H. Gutmann (Case Reports in Medicine, 2012)
Pilocytic astrocytoma (PA) is the most frequently encountered glial tumor (glioma or astrocytoma) in children. Recent studies have identified alterations in the BRAF serine/threonine kinase gene as the likely causative mutation in these childhood brain tumors. The majority of these genetic changes involve chromosome 7q34 tandem duplication, resulting in aberrant BRAF fusion transcripts. In this paper, we describe a novel KIAA1549:BRAF fusion transcript in a sporadic PA tumor associated with increased ERK activation and review the spectrum of BRAF genetic alterations in this common pediatric low-grade central nervous system neoplasm.